KAJIAN PEMBINAAN UMAT DALAM KEHIDUPAN BERAGAMA ANTARA PHDI KOTA TANGERANG DENGAN SDHD BANJAR TANGERANG - Artha, I Gusti Made; Suhardi, Untung; Budha, I Wayan (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2024)
Collaboration between Parisada Hindu Dharma Indonesia (PHDI) and Suka Duka Hindu Dharma (SDHD) in Tangerang, coaching is an essential component of human advancement. Nevertheless, the coaching program's lack of integration continues to hinder its execution, resulting in suboptimal community coaching outcomes. The primary issue with this research is that efforts to build communities in religious life between PHDI and SDHD Banjar Tangerang are not being carried out as effectively as they should. Use communication ethnography, which use qualitative analysis and data collecting methods like observation, interviews, and documentation, and neoclassical management theory to analyze the issue. The study's findings indicate that PHDI and SDHD Banjar Tangerang's implementation of community development in religious life is subpar, specifically: 1) There is a lack of coordination between PHDI and Banjar Tangerang's community development efforts. 2) Insufficient resources 3) In Banjar and PHDI Tangerang, the community and community leaders are not actively involved in community development. 4) The program's incompatibility with community development efforts in Banjar and PHDI Tangerang. 5) Banjar and PHDI Tangerang lack community development education and training. Initiatives to help people grow in their religious lives 1) PHDI and SDHD Banjar Tangerang cooperate. 2) Creation of a Community Development Program at PHDI Tangerang and Banjar. 3) Community development education and training at PHDI Tangerang and Banjar. 4) In Banjar and PHDI Tangerang, enhancing community involvement in community development. 5) Using social media and technology to promote community development at PHDI Tangerang and Banjar.